Stress, recovery, and team closeness: a case study of a 25-day ultra-endurance open-water swim in the Rhine River - Leis, O.; Walter, N.; Demirsöz, G.; Elbe, A.-M. (International Journal of Sport and Exercise Psychology, 2024)
This case study examines the dynamic changes in stress-recovery states experienced by a 34-year-old swimmer during a 25-day, 1259,5 km swimming event through the Rhine River. Stress and recovery states were assessed at baseline, each day of the event, and four days post-event on a seven-point Likert scale (0-6). At baseline, every third day, and post-event, the participant completed the German version of the Positive Affect and Negative Affect Schedule, reported perceived group closeness via visual analogue scales, and positive and negative events through open questions. A follow-up interview was conducted to better understand the participant`s experience of the stress-recovery relationship. The findings demonstrate above-average "Overall Stress" states (M = 3.21; SD = 0.93) and "Overall Recovery" states (M = 3.29; SD = 1.08) throughout the 25-day swimming event. The participant maintained higher positive than negative affect, and reported a sense of closeness to his support team throughout the event. This study highlights the dynamic relationship between stress and recovery, affect, and perceived group cohesion, which appears to be influenced by external factors reported by the participant (e.g., lack of current). The study also highlights the importance of personal resources, such as experience and the impact of external events (e.g., the lack of current or a damaged support team car) on the participant`s stress and recovery states. Overall, this study provides valuable insights into an ultra-endurance swim, outlining the importance of effective coping mechanisms in mitigating stress.